2012
DOI: 10.4040/jkan.2012.42.4.496
|View full text |Cite
|
Sign up to set email alerts
|

Depression of married and employed women based on social-role theory

Abstract: Purpose: This study was based on social-role theory, and purposes were to investigate (1) how depression and health determinants vary with married and employed women, and (2) what factors contribute to depression according to family cycle. Methods: A stratified convenience sample of 765 married and employed women was recruited during May to August 2010. Study variables of depression, socio-demographic threatening factors, psycho-stimulating factors, and social-role related factors were measured via a structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…On the other hand, depression in female workers may be influenced negatively by quality of life and result in lower work productivity in the workplace and rising maladjustment in daily working life [11]. Moreover, depression among married working women differs by psychostimulating and social role, in addition to occupational class and family life cycle [30], incivility of patients [31] and we should consider social roles for female workers to solve their psychosocial problems.…”
Section: Q3mentioning
confidence: 99%
“…On the other hand, depression in female workers may be influenced negatively by quality of life and result in lower work productivity in the workplace and rising maladjustment in daily working life [11]. Moreover, depression among married working women differs by psychostimulating and social role, in addition to occupational class and family life cycle [30], incivility of patients [31] and we should consider social roles for female workers to solve their psychosocial problems.…”
Section: Q3mentioning
confidence: 99%
“…Comparing to that of housewives, the self-rated health of unmarried mothers without a job was poor, depression was high, and married working women were the most stressed [15]. A study on Korean married women found that women rearing children who were involved in simple labor and sales service jobs were heavily influenced by the multi-role burden, and those in child-age families with professional careers were significantly affected by multi-role attachment [16]. A meta-analysis of studies involving work-family conflict, including multiple roles from 1999 to 2006, concluded that work-family conflicts had a negative impact on physical health, depression, and stress [17].…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal disease and gastrointestinal disease occur frequently in migrant workers who do strenuous physical labor. In addition, it is reported that married women engaged in simple labor or service ․ sales had high incidence of depression compared to in professional jobs [19]. Majority of our study subjects were engaged in manual labor (57.6%) or service ․ sales (26.6%), therefore similar health problems are expected to be common in working married immigrant women in Korea.…”
Section: Discussionmentioning
confidence: 96%